Conceptual proposals from psychoanalysis to understanding of psychosis in children - Barrera, Adriana (Pensando Psicología, 2010)
The article presents some refl ections about psychosis in children from different authors of some of the major psychoanalytic schools. For psychology, normality in abstract does not exist. To some extent it is a creation within the given possibilities and conquered acquisitions; is part of a continuum and from there it is addressed. Psychosis, as set out in this article, demonstrates a complex dynamic which refers directly, perhaps more than the theoretical pillars - technicians to meet with chaotic, disorganized that moves within the therapist concrete fl oor that has been built on muddy ground, showing you the more primitive ofhuman nature. Address the phenomenon of the psicotico from a particular dimension that not categorize psychosis for diagnostic purposes, but think about a mental problem area. Enunciaran fundantes concepts within the spectrum of psychosis of authors such as Freud, the French school, the I school, Melanie Klein and Donald Winnicott, of providing theoretical lights on the phenomenon and its possible psychoanalytic understanding.
Keywords: psychosis; forclusion; Oedipus; castration; identity